S plinom polnjeni paneli za visokoizolacijske stavbne ovoje 21. stoletja - Japelj Fir, Mojca (Gradbeni vestnik, 2012)
Oil price growth and otherwise limited natural resources have in recent year accelerated the development of novel energy saving materials and systems. The field of construction was no exception. Economically developed Europe has done a lot in the direction of the energy conservation. New mandatory guidelines and regulation were adopted that resulted in novel developments in the field of the building envelopes. In the paper, first a review of the state of the art in the field of the advanced thermal insulation is presented. In the following sections there is detailed description of the Trimo novel gas filled insulation panel Qbiss Air. The aspects of thermal, sound and fire performance are considered as well as tightness and serviceability limit states.
Keywords: fasade; izolacijski materiali; paneli